A Social Accounting Matrix for the Agricultural Sector of Pakistan (The Pakistan Development Review, 1987)
The purpose of this paper is to analyse the effect of alternative agricultural policies on production, consumption and income distribution within a social accounting, g framework. This is done by applying the social accounting multiplier analysis on the agricultural SAM for Pakistan for the year 1979-80. The paper focuses attention on the agricultural production sector, the related food producing industrial sectors and food consumption sectors, which are represented in the agriculture SAM by disaggregated accounts, while all the other production sectors in the economy have been aggregated into a single account. The paper is organized as follows: The SAM for the agricultural sector of Pakistan is presented in Section 2, followed by a discussion of multiplier decomposition in Section 3. Section 4 presents the results of the multiplier analysis and Section 5 gives a summary of the main results.